Mechanical Postconditioning Promotes Glucose Metabolism and AMPK Activity in Parallel with Improved Post-Ischemic Recovery in an Isolated Rat Heart Model of Donation after Circulatory Death - Arnold, Maria (Int J Mol Sci, 2020)
Donation after circulatory death (DCD) could improve donor heart availability; however, warm ischemia-reperfusion injury raises concerns about graft quality. Mechanical postconditioning (MPC) may limit injury, but mechanisms remain incompletely characterized. Therefore, we investigated the roles of glucose metabolism and key signaling molecules in MPC using an isolated rat heart model of DCD. Hearts underwent 20 min perfusion, 30 min global ischemia, and 60 minu reperfusion with or without MPC (two cycles: 30 s reperfusion—30 s ischemia). Despite identical perfusion conditions, MPC either significantly decreased (low recovery = LoR; 32 ± 5%; p < 0.05), or increased (high recovery = HiR; 59 ± 7%; p < 0.05) the recovery of left ventricular work compared with no MPC (47 ± 9%). Glucose uptake and glycolysis were increased in HiR vs. LoR hearts (p < 0.05), but glucose oxidation was unchanged. Furthermore, in HiR vs. LoR hearts, phosphorylation of raptor, a downstream target of AMPK, increased (p < 0.05), cytochrome c release (p < 0.05) decreased, and TNFα content tended to decrease. Increased glucose uptake and glycolysis, lower mitochondrial damage, and a trend towards decreased pro-inflammatory cytokines occurred specifically in HiR vs. LoR MPC hearts, which may result from greater AMPK activation. Thus, we identify endogenous cellular mechanisms that occur specifically with cardioprotective MPC, which could be elicited in the development of effective reperfusion strategies for DCD cardiac grafts.